(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the morphological patterns of pulmonary injuries among victims who died following road traffic accidents. Methods: This retrospective descriptive study included 87 fatal road traffic accident cases with documented pulmonary injuries identified through forensic examinations performed at the Department of Forensic Medicine, Hanoi Medical University, and the Department of Pathology, Viet Duc University Hospital, between January 1, 2018 and December 30, 2022. Data collected comprised demographic information, accident categories, causes of death, pulmonary injury patterns, and concomitant thoracic injuries. Statistical analyses were carried out using SPSS version 22.0 and Microsoft Excel 2010. Results: Among the 87 examined cases, males accounted for 74.7%, with the highest proportion occurring in the 15–29-year age group (37.9%). Motorcycle–car collisions represented the predominant accident type (51.7%). Fatalities were most frequently attributed to chest trauma associated with multiple injuries (43.7%). Pulmonary contusion was identified as the predominant pulmonary lesion (79.3%), followed by lung laceration (37.9%) and tracheobronchial disruption (10.3%). Pleural injuries, including hemothorax and hemopneumothorax, were present in 78.2% of cases. Rib fractures constituted the most common concomitant thoracic injury (72.4%). Conclusion: Fatal pulmonary injuries resulting from road traffic accidents demonstrate diverse morphological manifestations, occurring predominantly in males of working age. Pulmonary contusion represents the most prevalent lesion and is frequently accompanied by other thoracic injuries. The high proportion of chest trauma associated with multiple injuries highlights its important contribution to fatal outcomes. These findings provide useful forensic evidence for evaluating injury mechanisms and determining the cause of death.